BENZYLIDENE ACETALS OF HEPTONOLACTONES - Bichard, C; Bruce, I; Hughes, D; Girdhar, A; Fleet, G; Watkin, D (1993)
The preparation of 3,5-(R)-O-benzylidene-D-glycero-D-gulo-heptono-1,4-lactone, a readily available and powerful chiron, is described; other benzylidene derivatives of heptono-1,4-lactones are characterised. The X-ray crystal structure of 3,5(R):6,7(R)-di-O-benzylidene-D-glycero-D-gulo-heptono-1,4-lactone is reported. © 1993.